Shiitake dermatitis: the first case reported in Brazil Dermatite flagelada por shiitake, primeiro relato de caso no Brasil - André Ricardo Adriano; Martha Liliana Acosta; David Rubem Azulay; Carlos Daniel Quiroz; Samantha Rodrigues Talarico (Anais Brasileiros de Dermatologia, 2013)
Shiitake Dermatitis is often presented as papules and erythemato-violaceous linear streaks. It can be associated with bleomycin treatment, dermatomyositis and shiitake mushroom (Lentinus edodes). There is not any previous report concerning this rare etiology in our country. Shiitake is the second most consumed mushroom worldwide and it can cause flagellate erythema when ingested raw or half cooked. It has a higher incidence in Oriental countries because of their eating habits, this is the first case reported in Brazil, in a male patient that presented a cutaneous rash after consuming this raw mushroom. A dermatite flagelada é caracterizada por pápulas eritematosas lineares com aspecto de "chicotada". A etiologia pode ser associada ao uso de bleomicina, dermatomiosite e shiitake (Lentinus edodes). Este é o segundo cogumelo mais consumido no mundo e pode ser causa de dermatite flagelada quando ingerido cru ou mal cozido. Não há relatos nas literaturas de quadro de dermatite flagelada por shiitake em nosso país, reportamos o primeiro caso no Brasil de um paciente masculino que desenvolveu o quadro após a ingesta desse cogumelo cru.